Development of Audiovisual Media to Knowledge and Attitude of Students in Handwashing with Soap - Ilha Syam; Andi Tilka Muftiah Ridjal; Muh. Arfah (GLOBAL HEALTH SCIENCE GROUP, 2022)
Washing hands with soap is the handwashing act in 7 steps with soap and then rinsing with running water, to clean hands and break the chain of bacteria. In 2021, data obtained in Bunda Kasih Sudiang Elementary School showed the results of health measurements that 23 of 50 students had poor personal hygiene. This study aimed to recognize the effect of video media to knowledge and attitudes of students in washing hands act with soap. This was pre-experimental research with one group pretest-posttest study design without control group. The number of sample was 46 students in grades 4, 5 and 6 selected by total sampling. Data analysis applied Wilcoxon test which was previously analyzed by Kolmogorov-Smirnov normality test. The results revealed that before intervention, lack of knowledge category was 22 (47.8%), while after intervention, all respondents performed good knowledge by 46 (100%). Meanwhile, attitude before intervention was negative by 17 (37%), while after intervention, all students showed positive attitude by 46 (100%). Wilcoxon test results obtained value of knowledge by ρ = 0.000 < (0.05), and attitude by ρ = 0.000 < (0.05). It concluded that audiovisual media affected knowledge and attitude of washing hands with soap on students at SDS Bunda Kasih Sudiang. It is encouraged that audiovisual media may be applied as a promotive effort in the delivery of health education regarding handwashing with soap at school circumstances.